PENDIDIKAN GLOBAL BERBASIS KEARIFAN LOKAL - Wiwin Anggita Sari; Messi Messi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Globalization bring new challenges that must be answered by education. Need to change strategy education in preparing humans Indonesia in order to provide answers to the global challenges and opportunities globally. Method in this study using a research method descriptive qualitative. This study provides an overview of the global education through local wisdom. Study guide SMA 18 cities Palembang. Data collection techniques used in this study is observation, interviews, and documentation. Result of this research is a global education based local wisdom is required in order to improve the quality of education can compete in the middle of globalization. Global education very need to be applied to the current conditions. Global education based local wisdom is expected to create education competitive and innovative quality and reliable, which is able to compete in the middle of globalization.  Keywords- education, local wisdom, globalization